From Delta to Omicron—Genetic Epidemiology of SARS-CoV-2 (hCoV-19) in Southern Poland - Maria Miklasińska-Majdanik; Emilia Morawiec; Jolanta Bratosiewicz-Wąsik; Karol Serwin; Adam Pudełko; Michał Czerwiński; Anna Bednarska-Czerwińska; Miłosz Parczewski; Tomasz J. Wąsik (Pathogens, 2025)
Since severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was first reported in Wuhan, China, in December 2019, it has evolved, leading to variants that differ in their transmissibility, severity of disease, and susceptibility to therapy. Our goal was to describe the dynamics of the emergence of SARS-CoV-2 variants among the population of the southern part of Poland (Silesia) in the period from September 2021 to August 2022. Our results showed that, like in the rest of Poland or in neighboring countries (Czech Republic, Slovakia), Delta was replaced by the Omicron BA.1 variant, isolated for the first time in December 2021, and subsequently Omicron BA.2 and its derivative subvariants acquiring further mutations. Finally, in August 2022, only the BA.5.2.26 subvariant was present in Silesia. However, we noted differences in the dynamics of emergence and spread of some Omicron subvariants compared to the rest of Poland and the neighboring countries, which may be due to differences in population density or import of the virus from other regions.